Tarian Keberuntungan yang Rumit: Mengurai Paradoks Nasib Buruk - Maulana, Muhammad Fadli Maulana; Azzahra, Filosophia Azzahra; Gunawan, Ayub Gunawan; Santoso, Gunawan (Jurnal Pendidikan Transformatif, 2023)
The purpose of this study is to find out the Nova Effect perspective from the Vnvlan youtube channel entitled "What is Nova Effect? Flimsy Boundary of Unlucky and Lucky”. In this study, the researcher used a descriptive qualitative method by taking notes because the source of the data was obtained by listening to oral narratives. The results of this study explain that the Nova Effect teaches how something that happens to someone must have both good and bad sides. This study also says that sometimes something good brings something bad and something bad brings something good. The research started with the question What is the Nova Effect, How to avoid the Nova Effect, Are we destined to have bad luck. The study of the Nova Effect teaches us to be grateful for everything that has been ordained by God, to always be optimistic, and to stop overthinking.